Clothing practices of female freshmen dormitory residents of the University of the Philippines-Diliman - Calamba, Estrella E.
Large-scale migration from rural to urban communities is very apparent in the Philippines (Lauby, 1987). Young students coming from the provinces migrate to the National Capital Region and settle there until they graduate. They stay in the dormitories around the campus, away from their respective families and experience a lot of adjustments in terms of their clothing behavior. The objectives of this study were to describe the clothing practices of freshmen dormitory residents and explore on the factors that determine their way of acquisition, purchase, care, and disposal of clothes. The major findings of the study were: (1) Factors such as family income, monthly allowance, and food expenditure influenced the clothing expenditure of freshmen dormitory residents. (2) Clothing expenditure was significantly related to family income of the freshmen dormitory residents. (3) Clothing expenditure was significantly related to food expenditure of the freshmen dormitory residents. (4) Clothing expenditure was significantly related to monthly allowance of the freshmen dormitory residents. (5) Monthly allowance was significantly related to family income of the freshmen dormitory residents. (6) Frequency of acquiring new clothes was not significantly related to membership in organizations the freshmen dormitory residents. (7) Majority of the freshmen dormitory residents considered clothing practices in relation to aesthetic and conformity more often than their practices in relation to economy and function of clothes. Survey questionnaires were distributed to 60 freshmen dormitory residents of the University of the Philippines, Diliman. The respondents were selected by the researcher among residents of Kalayaan Residence Hall. Analysis of results was treated by means, frequency counts, averages and percentages. The chi-square was used in testing the hypotheses.